How do CSMs use AI to address challenges and improve the customer journeys in the European market? Exploring the Role of AI in Customer Success Management within the European Market - Flores Alania, Barashiel Ingrid (Universidad ESAN, 2025)
Customer Success Managers (CSMs) are vital in making companies customer-centric by building trust and ensuring value delivery. However, the impact of AI on their role remains unclear. This study explores how CSMs in Europe use AI to address challenges and enhance customer journey. Findings from interviews with twenty CSMs reveal challenges in managing customer expectations, data management, and organizational mindsets. While AI is helpful, its full potential is yet to be realized. The study offers insights for organizations adopting customer success practices and integrating AI.
Keywords: Gestión de éxito del cliente; Experiencia del cliente; Satisfacción del cliente; Inteligencia artificial; https://purl.org/pe-repo/ocde/ford#5.02.04